Identification of cognate genes among heterologous strains of group B rotavirus. - Eiden, J J (1992)
The genetic relatedness of group B rotavirus (GBR) strains has previously been documented by hybridization with probes derived from whole genomic sequences, but the relationship of individual genes of heterologous GBR strains has not been evaluated. Definition of cognate GBR genes would facilitate investigation of the determinants of group specificity, serotype identity, and neutralization epitopes. Therefore, we investigated the genetic relatedness of three GBR strains by means of Northern (RNA) blot hybridization with isotopically labeled probes prepared from each of the 11 genes of the IDIR strain of GBR. Under low-stringency conditions, hybridization between each of the IDIR gene probes and genomic RNA from the ADRV strain of GBR was observed. Genomic RNA obtained from a bovine strain of GBR hybridized with 9 of the 11 IDIR gene probes. In most cases, cognate genes of each of the GBR strains appeared to migrate to similar positions following polyacrylamide gel electrophoresis. However, the electropherotype positions of GBR genes 5, 6, and 7 were different for each of the three GBR strains. Identification of these genomic segments among GBR strains should prove helpful in future evaluations of GBR structure and function.